2018
DOI: 10.1002/ijc.31539
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer risk in HPV‐positive women after a negative FAM19A4/mir124‐2 methylation test: A post hoc analysis in the POBASCAM trial with 14 year follow‐up

Abstract: DNA methylation analysis of cervical scrapes using FAM19A4 and mir124‐2 genes has shown a good clinical performance in detecting cervical cancer and advanced CIN lesions in need of treatment in HPV‐positive women. To date, longitudinal data on the cancer risk of methylation test‐negative women are lacking. In our study, we assessed the longitudinal outcome of FAM19A4/mir124‐2 methylation analysis in an HPV‐positive screening cohort with 14 years of follow‐up. Archived HPV‐positive cervical scrapes of 1,040 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 44 publications
7
90
0
Order By: Relevance
“…Currently available methylation markers have shown good clinical performance in the detection of advanced transforming precursor lesions and CC in hrHPV‐positive women. In addition, results from a large follow‐up study have shown a low CC risk for hrHPV‐positive women with a negative FAM19A4/miR124‐2 triage test result, offering an objective triage test in hrHPV‐based screening programs . We found that FAM19A4 has the major contribution to predicting the presence of HSIL/CIN3 as compared to miR124‐2.…”
Section: Discussionmentioning
confidence: 58%
“…Currently available methylation markers have shown good clinical performance in the detection of advanced transforming precursor lesions and CC in hrHPV‐positive women. In addition, results from a large follow‐up study have shown a low CC risk for hrHPV‐positive women with a negative FAM19A4/miR124‐2 triage test result, offering an objective triage test in hrHPV‐based screening programs . We found that FAM19A4 has the major contribution to predicting the presence of HSIL/CIN3 as compared to miR124‐2.…”
Section: Discussionmentioning
confidence: 58%
“…Specimens with sufficient leftover material were randomly selected from local cohorts. It was verified within each test situation that the QIAsure Methylation Test positivity rate was comparable to the known positivity rate in an HPV‐positive screening cohort, that is, test situation 1:39%; test situation 2:30%; and test situation 3:31%.…”
Section: Methodsmentioning
confidence: 81%
“…A key aspect is the efficient detection of cervical carcinomas and advanced CIN lesions, that is, CIN2/3 lesions associated with a duration of the preceding hrHPV infection of >5 years, which have increased methylation levels and many chromosomal aberrations (“cancer‐like” (epi)genetic profile), and have therefore been considered to have an expected high short‐term risk of progression to cancer . A negative QIAsure Methylation Test, on the other hand, indicates a low cervical cancer risk over the subsequent 14 years in hrHPV‐positive women …”
Section: Introductionmentioning
confidence: 99%
“…In the HPV arms of the trial, S5 triage would have reduced clinician visits and screen tests as more high‐grade disease would have been detected at baseline, thus simplifying the screening algorithm and potentially reducing loss to follow‐up. In future, methylation markers may be shown to preferentially detect advanced lesions with a high short term risk of cervical cancer; indeed, a recent study from the POBASCAM trial showed that women negative for DNA methylation had a low future risk of cervical cancer over the subsequent 14 years …”
Section: Discussionmentioning
confidence: 99%